PENGARUH PELATIHAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PERDANA PRIMA BHAKTI MANDIRI DI CIPUTAT TANGERANG SELATAN - Watimah; Mulyani, Sri (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of job training and work discipline on employee performance at PT. Perdana Prima Bhakti Mandiri. This research uses quantitative methods. The sampling technique used saturated sampling and the sample obtained in this study was 65 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research show that: (1) Job training has a positive and significant effect on employee performance with a regression of Y = 10.159 +0.758 X1, a correlation value of 0.734, meaning the two variables have a strong level of relationship. The coefficient of determination value is 53.8%. Hypothesis test results showed that the t count was greater than the t table or 8.567 > 1.998 and a significance value of 0.001 < 0.05. Thus, H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between job training and employee performance. (2) Work discipline has a positive and significant effect on employee performance with a regression of Y = 6.771 + 0.835X2, a correlation value of 0.779, meaning that the two variables have a strong level of relationship. The coefficient of determination value is 60.6%. Hypothesis testing obtained that the t count was greater than the t table or 9.853 > 1.998 and a significance value of 0.001 < 0.05. Thus, H0 is rejected and H2 is accepted, meaning that there is a positive and significant influence between work discipline and employee performance. (3) Job training and work discipline have a positive and significant effect on employee performance with the regression equation Y = 2.258 + 0.398X1 + 0.559X2, the correlation coefficient value is 0.830, meaning that the independent variable and the dependent variable have a strong level of relationship. The coefficient of determination value is 68.9% while the remaining 31.1% is influenced by other factors. hypothesis testing obtained calculated f is greater than f table or 68.521 > 2.750 and a significance value of 0.001 < 0.05. Thus, H0 is rejected and H3 means that there is a simultaneous positive and significant influence between job training and work discipline on employee performance at PT. Perdana Prima Bhakti Mandiri.